PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS V SDN 52 PARUPUK TABING KOTA PADANG - Dzakiya Zahra Fadhila; Yesi Anita; Rafhi Febryan Putera; Hana Shilfia Iraqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the improvement of students' learning outcomes in Pancasila Education learning using the Problem-Based Learning model in Class V of SDN 52 Parupuk Tabing, Padang City. This research is a Classroom Action Research (PTK) that employs both qualitative and quantitative approaches. The study was conducted in two cycles, cycle I consisted of two meetings, and cycle II consisted of one meeting. The research subjects were the teacher (researcher) and 20 students, consisting of 9 male and 11 female students. The results of the study showed improvements in: (1) The average score of the teaching module planning in cycle I was 87.51% (Good), which increased to 95.83% (Very Good) in cycle II; (2) The average teacher activity implementation score in cycle I was 83.9% (Good), which increased to 96.4% (Very Good) in cycle II; (3) The assessment of students’ learning outcomes in cycle I had an average score of 73.5% (Fair), which improved to 93.2% (Very Good) in cycle II.